1983
DOI: 10.1029/rs018i006p01325
|View full text |Cite
|
Sign up to set email alerts
|

VHF radar signals scattered from the equatorial mesosphere

Abstract: Radio signals scattered from the equatorial mesosphere above Jicamarca, Peru have been studied. The scattered power level is dependent on look angle in the lower parts of the mesosphere. Indications are that this aspect sensitivity in the received signal cannot be adequately explained by specular reflection from stratified layers. Interferometer studies of the scattered signal have shown that there are structures in the mesosphere that have vertical velocity that varies in the horizontal direction within the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
6
13
1
Order By: Relevance
“…Negative correlations were reported for the lower mesosphere, suggestive of an increasing role for reflections at heights closer to the stratosphere, or the possibility of inertial range turbulence as suggested by Røyrvik (1985). Subsequent Jicamarca measurements conducted with a 2 km resolution (Røyrvik, 1983) showed similar and consistent results, including predominantly "aspect sensitive" returns from below 75 km.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…Negative correlations were reported for the lower mesosphere, suggestive of an increasing role for reflections at heights closer to the stratosphere, or the possibility of inertial range turbulence as suggested by Røyrvik (1985). Subsequent Jicamarca measurements conducted with a 2 km resolution (Røyrvik, 1983) showed similar and consistent results, including predominantly "aspect sensitive" returns from below 75 km.…”
Section: Introductionsupporting
confidence: 62%
“…This is in contrast to earlier studies of Fukao et al (1980) and Røyrvik (1983) conducted with vertical beams. These earlier studies showed a significant amount of negative correlations in the lower mesosphere below 75 km.…”
Section: Vertical Beam Data and Aspect Sensitivitycontrasting
confidence: 54%
See 3 more Smart Citations